Production of Curcumin-loaded Nanoemulsion from Curcuma longa (Turmeric) Extract and Its Antimicrobial Activity - Mohd Shah, Nurhaslinda; Mohd Kassim, Angzzas Sari; A. Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2022)
Microorganisms are capable of causing variety of diseases in humans, most particularly skin infections. This is because skin acts as the first shield, protecting our bodies from foreign organisms or any toxins. Antimicrobial topical creams may be used to treat wound infection caused by these microbes. The majority of topical medications available on the market to treat skin-related diseases are formulated via synthetic processes that involve the use of chemicals and may result in adverse effects. Thus, this research aims to investigate the potential of curcumin-loaded nanoemulsion as natural antimicrobial agents to substitute synthetic antimicrobials in formulated creams, with the hope of advancing the pharmaceutical industry using Malaysia herb plants. Based on this study, nanoemulsion was developed via oil-in-water method using Tween 20 and black pepper oil with different ratio and fabricated at two heating temperatures (70 °C and 75 °C). Then, the characterization such as particle diameter size, pH and colour are evaluated. Next, the antimicrobial analysis was conducted using disk diffusion method against E. coli, S. aureus, and A. niger. The findings shows that, the sample prepared by heating at 75 °C shows the best characterization with the smallest particle diameter size (320 nm), and the most suitable pH (5.76) for skin application. The results obtained also shows that the nanoemulsion with Curcuma Longa extract has a great potential to inhibit the growth of microorganism. However, Curcuma longa was more susceptible against S. aureus compared with E. coli as well as A. niger. Besides, nanoemulsion heating at 75 °C shows greater zone of inhibition compared with heating temperature 70 °C against E.coli, S. aureus, A. niger (11.5 ± 0.7, 13.5 ± 0.7, 11.5 ± 0.7) nm. Lastly, findings from this research can contribute to the development of a safe and greener alternative with plant ingredients in the formulation of cream, thereby advancing the health care industry.